The Concept and Essence of Independent Student Work (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article addresses current issues and innovations in the organization of in-dependent student work. It analyzes various problems of self-education, possi-ble options for organizing successful independent work from the perspective of scientists and philologists on a global scale. The role of effective interaction be-tween teachers and students within the framework of independent learning is discussed. Various scientific studies are analyzed, along with new interactive approaches to organizing independent student work, taking into account mod-ern technologies. The research of many renowned scholars and philologists is examined, including the studies of A.M. Novikov, who emphasizes that the principle of self-organization in educational activities has become one of the leading principles of domestic education. The research of S.S. Amirova and other scholars, who focused on university students and professionals enhanc-ing their qualifications, is also explored.